(untitled) (Marketing Jurnali, 2025)
This article analyzes the directions of sustainable and innovative development of the textile industry. Based on global experience, it examines the role of this sector in the world economy, the processes of digitalization, the implementation of the “green economy” principles, compliance with ESG standards, and the introduction of innovative technologies. The study also explores Uzbekistanʼs state policy aimed at modernizing the textile and apparel industry, producing high value-added products under the “Textile Industry 2030” strategy, enhancing export potential, and developing the cluster system.